Influence of B-site compositional homogeneity on properties of (K0.44Na0.52Li0.04)(Nb0.86Ta0.10Sb0.04)O3-based piezoelectric ceramics - Ramajo, Leandro Alfredo (2014)
The effect of B-site compositional homogeneity on microstructure, piezoelectric properties and dielectric behaviour of lead-free piezoelectric ceramics, (K0.44Na0.52Li0.04) (Nb0.86Ta0.10Sb0.04)O3, is investigated. The B-site compositional homogeneity is evaluated by using an intermediate precursor obtained by solid state reaction between adequate amounts of Nb2O5, Ta2O5 and Sb2O5, calcined at 1350 °C and attrition milled. The B-site precursor powder is mixed with alkaline carbonates to synthesize perovskite powders and, finally, sinter piezoceramics. X-ray diffraction and Raman spectroscopy reveal the formation of a perovskite phase, although tetragonal tungsten-bronze structure is detected as minor secondary phase. Ceramics processed by using B-site precursor show different crystalline structure as a function of sintering conditions or K/Na ratio. The B-site precursor route produces thus lower piezoelectric properties, but the control of alkali volatilization by using sintering powder bed resulted in a relevant decrease of dielectric losses that favours the d33 enhancement.